Additions to the orchid flora of Belize, Central America - Sayers, Brendan; Du Plooy, Heather (Lankesteriana: International Journal on Orchidology, 2016)
T h e N a t i o n a l B o t a n i c G a r d e n s , G l a s n e v i n , D u b l i n , I r e l a n d h a v e t r a v e l l e d t o B e l i z e , C e n t r a l America on five expeditions for the main purpose of collecting living specimens of Orchidaceae. Four of the expeditions were in conjunction with Belize Botanic Gardens. As a result of these expeditions 17 new records for Orchidaceae are being added to the published flora.